Risk Stratification for Serosal Invasion Using Preoperative Predictors in Patients with Advanced Gastric Cancer - Park, Sung-Sil (The Korean Gastric Cancer Association, 2012)
PURPOSE: Although serosal invasion is a critical predisposing factor for peritoneal dissemination in advanced gastric cancer, the accuracy of preoperative assessment using routine imaging studies is unsatisfactory. This study was conducted to identify high-risk group for serosal invasion using preoperative factors in patients with advanced gastric cancer. MATERIALS AND METHODS: We retrospectively analyzed clinicopathological features of 3,529 advanced gastric cancer patients with Borrmann type I/II/III who underwent gastrectomy at Korea Cancer Center Hospital between 1991 and 2005. We stratified patients into low- (≤40%), intermediate- (40~70%), and high-risk (>70%) groups, according to the probability of serosal invasion. RESULTS: Borrmann type, size, longitudinal and circumferential location, and histology of tumors were independent risk factors for serosal invasion. Most tumors of whole stomach location or encircling type had serosal invasion, so they belonged to high-risk group. Patients were subdivided into 12 subgroups in combination of Borrmann type, size, and histology. A subgroup with Borrmann type II, large size (≥7 cm), and undifferentiated histology and 2 subgroups with Borrmann type III, large size, and regardless of histology belonged to high-risk group and corresponded to 25% of eligible patients. CONCLUSIONS: This study have documented high-risk group for serosal invasion using preoperative predictors. And risk stratification for serosal invasion through the combination with imaging studies may collaboratively improve the accuracy of preoperative assessment, reduce the number of eligible patients for further staging laparoscopy, and optimize therapeutic strategy for each individual patient prior to surgery.